KASUS PT PANCA PUJI BANGUN DI SURABAYA DIKAITKAN DENGAN PASAL 91 AYAT (1) JO PASAL 185 UNDANG-UNDANG NOMOR 23 TENTANG KETENAGAKERJAAN - Eka Sukarini, Eri (Yustitia, 2018)
A work relationship is a relationship between a worker / laborer and an employer / employer that occurs after the employment agreement or based on a work agreement that has elements of work, wages and orders. Therefore, legal relations between workers and employers are bound by the existence of a work agreement. The purpose of this article is to report how to resolve industrial relations; to reveal wages according to the Labor Law; to report cases related to employment. The findings and discussion indicate that industrial relations disputes are differences of opinion which result in conflicts between employers or joint entrepreneurs with workers / laborers or trade unions because of disputes regarding rights, interests, termination of employment, and disputes between trade unions in one company . The procedures for resolving Industrial Relations Disputes (PHI) are in accordance with Law Number 2 Year 2004 concerning Settlement of Industrial Relations Disputes (PHI Law), namely: Bipartite Negotiations, Tripartite Negotiations, Mediation, Councils, Arbitration, Industrial Relations Court. From the case of PT Panca Puji Bangun regarding the wages of workers / laborers not in accordance with Surabaya City Minimum Wages, the case was resolved through the Industrial Relations Court (PHI).